2010
DOI: 10.1002/hbm.20892
|View full text |Cite
|
Sign up to set email alerts
|

Functional 5‐HT1a receptor polymorphism selectively modulates error‐specific subprocesses of performance monitoring

Abstract: Our study investigates the dependence of response monitoring and error detection on genetic influences modulating the serotonergic system. This was done using the event-related potentials (ERPs) after error (Ne/ERN) and correct trials (Nc/CRN). To induce a sufficient amount of errors, a standard flanker task was used. The subjects (N = 94) were genotyped for the functional 5-HT1A C(-1019)G polymorphism. The results show that the 5-HT1A C(-1019)G polymorphism specifically modulates error detection. Neurophysiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 52 publications
5
30
0
Order By: Relevance
“…The current results confirm previous observations that error responses specifically increase ␦-frequency band activity (Yordanova et al, 2004b;Beste et al, 2007Beste et al, , 2009Beste et al, , 2010aKolev et al, 2009). The results suggest also that BDNF gene variation might selectively modulate error-specific processes, but not processes of general motor response monitoring, since genotype effects were restricted to the ␦-frequency band, which was predominantly active on error, but not on correct trials (Yordanova et al, 2004b).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The current results confirm previous observations that error responses specifically increase ␦-frequency band activity (Yordanova et al, 2004b;Beste et al, 2007Beste et al, , 2009Beste et al, , 2010aKolev et al, 2009). The results suggest also that BDNF gene variation might selectively modulate error-specific processes, but not processes of general motor response monitoring, since genotype effects were restricted to the ␦-frequency band, which was predominantly active on error, but not on correct trials (Yordanova et al, 2004b).…”
Section: Discussionsupporting
confidence: 82%
“…The influence of genetic factors on error processing and response monitoring functions has frequently been studied in the past (Klein et al, 2007;Krämer et al, 2007;Beste et al, 2010a). Until now, no study examined the role of neurotrophins for these im- portant cognitive functions.…”
Section: Discussionmentioning
confidence: 99%
“…For cognitive control processes (i.e., error monitoring) time-frequency analyses have shown that especially oscillations in the delta frequency band are empowered in cases, where demands on cognitive control and behavioural monitoring are increased (e.g. Yordanova et al, 2004;Beste et al, 2007Beste et al, , 2010b. In addition, plenty of evidence suggests that the alpha frequency band may also be relevant for the cognitive processes assessed in the present study.…”
Section: Introductionmentioning
confidence: 90%
“…For example, normal subjects with the GG-genotype showed reactions associated with increased negative emotionality in a reward-punishment paradigm [133]. Recent studies indicate that the presence of the G-allele in normal subjects associated with specific impairments in cognitive ability, including error and attentional processing [134,135]. These findings in normal subjects suggest that the rs6295 polymorphism generates impairments in emotional and cognitive processing that lead to an inability to handle stressful situations, leading to an increased susceptibility to depression and anxiety (Fig.…”
Section: -Ht1a Promoter Polymorphisms and Mental Illnessmentioning
confidence: 99%